THE BREEDING TECHNIQUE OF TAWES FISH (Barbonymus gonionotus) IN GOVERNMENT UNIT OF TECHNICAL IMPLEMENTING SERVICE OF FRESHWATER AQUACULTURE IN JEMBER - Nisa, Andina Chairun; Khairunissa, Ade Fitri (Politeknik Kelautan dan Perikanan Sidoarjo, 2023)
The tawes fish (Barbonymus gonionotus) is one of the natural aquatic wealth of Indonesia has thick meat and a high market price. It meat boasts a higher protein content of 18.43% compared to carp (16%) and tilapia (18.72%). Tawes fish has the characteristic of being economically valuable and has the potential to be cultivated because it does not require too much land and can be cultivated throughout the year. In order to obtain good quality fish seeds in large quantities, the operational activities of fish breeding must be carried out carefully and planned. The activities of fish breeding began with the preparation of the pond, the selection of broodstock, spawning, hatching, larval rearing, and harvesting. Some parameters that can be measured in hatchery activities include fecundity, fertilization rate (FR), hatching rate (HR), food conversion rate (FCR) and survival rate (SR). Data collection techniques conducting direct observation, interviews, or observations about Pond preparation, broodstock selection, spawning, larval rearing, feeding and harvesting with the parameters that were measured in fish breeding activities were fecundity, Fertilization Rate (FR), Hatching Rate (HR), Food Conversion Ratio (FCR), and Survival Rate (SR). Based on the results of this research the fecundity value obtained was 24,489 eggs/parent, FR was 54%, HR was 65%, FCR was 3.9, and SR 60%.